Isolation and characterization of nitrogen-fixing bacteria from soil sample in Dhaka, Bangladesh (Stamford Journal of Microbiology, 2021)
Biological nitrogen (N2) fixation is very essential for limiting the growth of plants and agricultural crops. The present study was conducted to potentially isolate N2-fixing bacteria from garden soil sample at Stamford University Bangladesh, Siddeswari, Dhaka. Here, we used culture-dependent method to perform this experiment. Firstly, we collected garden soil sample, diluted and inoculated in N2-free Jensen’s media by maintaining the aseptic procedure. We obtained 5 different colonies from soil samples. We cultured the isolates in N2-free Jensen’s media containing bromothymol blue (BMB) and also, in Yeast Extract Mannitol Agar (YEMA) media containing congo red to confirm nitrogen fixation capacity. We collected the colony characteristics of all the isolates. Only 1A isolate showed good growth after 24 h of incubation among all the isolates. We performed ammonification test with Nessler reagent to confirm N2-fixing ability for our selected isolates. The 1A isolate was positive in ammonification test. Culture, microscopy and biochemical tests were performed to identify isolate 1A. This isolate was presumptively identified as Azotobacter sp. In the present study, Azotobacter sp. that was isolated from the soil sample was found to be a potential N2-fixing bacterium. Isolate 1A can be used for N2-fixation to boost production of crops.Stamford Journal of Microbiology, Vol.11 (1) 2021: 11-13